HERMENEUTIKA DILTHEY DAN KONTRIBUSI TERHADAP METODE SOSIO HISTORI KRITIS DALAM MENAFSIR KITAB SUCI - Danny Sally Ririhena (IAKN Ambon, 2018)
The issue of fusion is often the main obstacle in trying to understand the scriptures even though it is realized that the development of the world of interpretation is increasingly rapid, but increasingly people are trapped in the powerlessness of interpreting the text Scripture. Dilthey's hermeneutics and contributions to the critical socio-historical method of interpreting scriptures are interesting issues to be discussed in this article by referring to two fundamental questions, namely: 1) What is Dilthey's rationale and the methods he uses in understanding historical reality? 2). What is the relevance of Dilthey's hermeneuit in the world of biblical interpretation. Answering the question, this study used the literature study method as an effort to find literature sources and documents as reference sources to understand Dilthey's work in relation to the issues to be discussed. The results of the research reveal that Dilthey's ideas about experience, expression and is an important idea in understanding historical reality as an actor who is also part of historicity. Based on three basic things, the concept of verstehen emerged as a way to interpret historical reality. The development of socio-historical interpretations in the process of interpreting the scriptural texts was contributed by Hemeneutic Dilteyh.